2021
DOI: 10.3390/jcm10102114
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Superficial and Deep Cutaneous Microcirculation Due to Axillary Plexus Anesthesia Impaired by Smoking

Abstract: Background: Understanding microvascular physiology is key to any reconstructive procedure. Current concepts in anesthesia increasingly involve regional peripheral nerve blockade during microvascular reconstructive procedures. Whereas favorable effects on perfusion due to these techniques have been reported earlier, little evidence focusing on its effects in most peripheral vascular compartments is available. Methods: A total of 30 patients who were to receive axillary plexus blockade (APB) were included. Micro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…All the centres performed replantation surgery under continuous plexus anaesthesia. It enables optimal blood pressure for distal tissue perfusion, and it can directly promote peripheral vasodilatation ( Bosselmann et al., 2021 ). The peripheral vasodilatation is particularly important in children, because they seem to have a tendency to develop vasospasm peripheral vessels ( Duteille et al., 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…All the centres performed replantation surgery under continuous plexus anaesthesia. It enables optimal blood pressure for distal tissue perfusion, and it can directly promote peripheral vasodilatation ( Bosselmann et al., 2021 ). The peripheral vasodilatation is particularly important in children, because they seem to have a tendency to develop vasospasm peripheral vessels ( Duteille et al., 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tobacco use is linked to over 60 diseases [ 3 ], and it has long been common knowledge that tobacco use has a wide range of adverse effects on the circulatory system [ 42 ]. The microcirculation of the skin is also affected by cigarette smoke exposure [ 43 , 44 ]. Cyril et al demonstrated that the vasodilatory response of the skin microvasculature is significantly impaired in people who have smoked for years [ 45 ], and an in vivo study by Sophie-Élise et al also showed that angiogenesis was impaired considerably in mice exposed to cigarette smoke following surgically induced hindlimb ischemia.…”
Section: Discussionmentioning
confidence: 99%